Pragmatic inquiry : critical concepts for social sciences - Bowen, John R. (John Richard), 1951-; Dodier, Nicolas, 1957-; Duyvendak, Jan Willem; Hardon, Anita (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book examines a range of critical concepts that are central to a shift in the social sciences toward 'pragmatic inquiry', reflecting a twenty-first century concern with particular problems and themes rather than grand theory. Taking a transnational and transdisciplinary approach, the collection demonstrates a shared commitment to using analytical concepts for empirical exploration, and a general orientation to research that favors an attention to objects, techniques, and practices. The chapters draw from broad-based and far-reaching social theory in order to analyze new, specific challenges, from grasping the everyday workings of markets, courtrooms and clinics, to inscribing the transformations of practice within research disciplines themselves. Each contributor takes a key concept, and then explores its genealogies and its circulations across scholarly communities, as well as its proven payoffs for the social sciences, and, often, critical reflections on its present and future uses. This carefully crafted volume will significantly expand and improve the analytical repertoires or toolkits available to social scientists, including scholars in sociology or anthropology, and those working in science and technology studies, public health, and related fields"--
OCLC-licensed vendor bibliographic record.
Keywords: Social sciences -- Research -- Methodology; SOCIAL SCIENCE / Anthropology / General